2014
DOI: 10.1093/pcp/pcu205
|View full text |Cite
|
Sign up to set email alerts
|

MdMYB9 and MdMYB11 are Involved in the Regulation of the JA-Induced Biosynthesis of Anthocyanin and Proanthocyanidin in Apples

Abstract: Anthocyanin and proanthocyanidin (PA) are important secondary metabolites and beneficial to human health. Their biosynthesis is induced by jasmonate (JA) treatment and regulated by MYB transcription factors (TFs). However, which and how MYB TFs regulate this process is largely unknown in apple. In this study, MdMYB9 and MdMYB11 which were induced by methyl jasmonate (MeJA) were functionally characterized. Overexpression of MdMYB9 or MdMYB11 promoted not only anthocyanin but also PA accumulation in apple callus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
254
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(266 citation statements)
references
References 54 publications
12
254
0
Order By: Relevance
“…Arabidopsis AtMYB75, Arabidopsis AtMYB90 and its homologous gene MdMYB1 in apple are crucial regulators of light-induced anthocyanin biosynthesis, and their degradation requires the CONSTITUTIVELY PHOTOMORPHOGENIC1 (COP1) ubiquitin-dependent pathway in the dark4142. Similarly, several recent reports have described jasmonate-mediated anthocyanin accumulation through upstream control of MBW complex activity3943. However, these studies do not fully explain the underlying mechanism of up-regulation and down-regulation of anthocyanin regulators in specific environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis AtMYB75, Arabidopsis AtMYB90 and its homologous gene MdMYB1 in apple are crucial regulators of light-induced anthocyanin biosynthesis, and their degradation requires the CONSTITUTIVELY PHOTOMORPHOGENIC1 (COP1) ubiquitin-dependent pathway in the dark4142. Similarly, several recent reports have described jasmonate-mediated anthocyanin accumulation through upstream control of MBW complex activity3943. However, these studies do not fully explain the underlying mechanism of up-regulation and down-regulation of anthocyanin regulators in specific environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…JAs mediate responses to wounding, and their capacity to stimulate pigmentation may be related to this role (Creelman and Mullet, 1997). An et al (2015) reported that the expression of the MYB TF genes MdMYB9 and MdMYB11 increased significantly compared to that of MdMYB1 in 'Orin' apple calli in response to JA treatment and in 'Gala' leaves in response to wounding. Subsequent functional analyses demonstrated that these two MYB TFs bound to the promoter regions of some flavonoid biosynthetic genes and induced anthocyanin accumulation in calli in the presence of JA.…”
Section: ) Plant Hormonesmentioning
confidence: 99%
“…These regulators form an MBW complex that binds to promoters and activates transcription of structural genes of the anthocyanin biosynthetic pathway (Rahim et al, 2014; Li et al, 2016). The role of MBW in anthocyanin biosynthesis has been elucidated in fruit trees such as grape (Kobayashi et al, 2002, 2004; Walker et al, 2007), Chinese bayberry (Niu et al, 2010; Liu et al, 2013a,b), mangosteen (Palapol et al, 2009), blood orange (Crifò et al, 2011; Butelli et al, 2012), kiwifruit (Fraser et al, 2013), litchi (Lai et al, 2014, 2016), sweet cherry (Shen et al, 2014), apple (Takos et al, 2006; Espley et al, 2007; Xie et al, 2012; Chagné et al, 2013; An et al, 2015), and peach (Rahim et al, 2014; Zhou et al, 2014; Tuan et al, 2015). …”
Section: Introductionmentioning
confidence: 99%